2020
DOI: 10.1108/jacpr-04-2020-0489
|View full text |Cite
|
Sign up to set email alerts
|

Fear of terror and employees’ behaviour in terrorist-ridden areas

Abstract: Purpose This study aims to investigate the impact of fear of terror (FOT) on employee organizational commitment (OC) working in terror-induced areas through examining the role of rumination as a mediator and perceived organization support (POS) as a moderator. Design/methodology/approach The authors develop a model in which the mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In existing research, employee higher efforts at the workplace cause their health as they receive no appropriate rewards in return. Under those circumstances, the feeling of physical danger and mental tiredness is pervasive in dangerous areas (Bader and Manke, 2018 ; Soomro et al, 2020 ). According to the literature, Bader and Berg ( 2014 ) also reported a significant negative relationship between sensitivity to terrorism, with compensation for expatriates (−0.113 * ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In existing research, employee higher efforts at the workplace cause their health as they receive no appropriate rewards in return. Under those circumstances, the feeling of physical danger and mental tiredness is pervasive in dangerous areas (Bader and Manke, 2018 ; Soomro et al, 2020 ). According to the literature, Bader and Berg ( 2014 ) also reported a significant negative relationship between sensitivity to terrorism, with compensation for expatriates (−0.113 * ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between employee job stress working in terrorism-ridden areas is less explored (Bader et al, 2015 ). The extant literature on the effects of terrorism on employee behavior and the working practices of organizations is limited and empirical evidence is relatively low in the context of Pakistan (Soomro et al, 2020 ). The present study attempts to address this gap by studying Pakistan's businesses that are affected by terrorist incidents.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological effects resulting from terrorism are not limited to those directly exposed to terrorism; subjective perception also plays a role (Soomro et al, 2020). Several studies have documented the negative consequences of working in a harmful working environment on employees’ work and health-related factors (e.g., De Clercq et al, 2017; Soomro et al, 2020). Burke and Cooper (2008) argued that working in an environment where terrorist incidents occur might ignite fear of death and cause well-being issues.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, little published data exists on the concept of employee STT in the workplace setting, especially in the context of terrorism-ridden areas. According to Soomro et al (2020), terrorism-ridden areas are added drivers of stress for employees. Similarly, McNally et al (1987) conducted an experimental study and found that individuals who were more sensitized to distressing events experienced greater stress as compared to those who were less sensitized to distressing events.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation